APLIKASI KONSULTASI DOKTER-PASIEN SECARA ONLINE BERBASIS ANDROID MENGGUNAKAN REACT NATIVE - Mochamad Wisuda Sardjono; Nicolas Sanjaya (Jurnal Sistem Informasi dan Informatika (Simika), 2023)
The use of communication technology has penetrated into every field, including those related to medical consulting services. Smartphone devices not only function as a verbal communication tool, but can be used for online communication. With the development of computer programming languages, smartphone devices can be used more widely to serve consultations about health. Javascript is a programming language that is widely used in developing mobile applications. The React Native framework is used to design mobile applications so that they are easy to use via smartphone devices without going through a web application. In this study UML is used as an application design method and firebase as a data storage medium. The trials were carried out using BlackBox Testing on 4 smartphone devices based on the Android operating system with different specifications. In addition, trials were also carried out on every function in the Doctor-Patient Consultation application involving 25 respondents by providing an assessment. The test results show that the use of the React Native framework maximizes the design of Android-based mobile applications. Of the 4 smartphone devices, all functions in the application went well, apart from that, 25 respondents who gave an assessment of more than 65% stated that they agreed and strongly agreed with each statement regarding the application.